2016
DOI: 10.1016/j.aott.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Dual plating for fixation of humeral shaft fractures: A mechanical comparison of various combinations of plate lengths

Abstract: ObjectiveThe role of plate configuration was found inconclusive on the biomechanical effects of the plate size and hole number for dual plate constructions in humeral shaft fractures. The purpose of this study was to test the biomechanical stability of various dual plate constructions.MethodsTwenty-four left humeri (4th Generation Composite Humerus, Sawbones, Malmö, Sweden) with comminuted midshaft humeral fracture were used. Four groups of plate constructs were tested: laterally fixed 8-hole locking plate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…They combined a laterally fixed 8-hole plate with a plate containing 4 or 6 holes or with another 8-hole plate placed at an angle of 90°t o the first plate. The groups with additional 4-and 6-hole plate had biomechanically comparable values, while the two 8-hole plate construction was the most stable [36]. In a finite-element study on plate location with 2 plates used to treat humeral shaft fractures, the authors evaluated altogether 5 different groups.…”
Section: Humeral Shaftmentioning
confidence: 99%
“…They combined a laterally fixed 8-hole plate with a plate containing 4 or 6 holes or with another 8-hole plate placed at an angle of 90°t o the first plate. The groups with additional 4-and 6-hole plate had biomechanically comparable values, while the two 8-hole plate construction was the most stable [36]. In a finite-element study on plate location with 2 plates used to treat humeral shaft fractures, the authors evaluated altogether 5 different groups.…”
Section: Humeral Shaftmentioning
confidence: 99%
“…Posterior plating has biomechanical advantages because the plate is applied on the tension side of the humerus, and lateral plating is also widely used for humeral shaft fractures 24 . However, some researchers are concerned that a single plate provides inadequate fixation and is inferior to dual‐plate fixation 25,26 . The present study retrospectively analyzed the DASH scores of patients who received one of three possible plating methods for arm wrestling fractures.…”
Section: Discussionmentioning
confidence: 99%
“…24 However, some researchers are concerned that a single plate provides inadequate fixation and is inferior to dual-plate fixation. 25,26 The present study retrospectively analyzed the DASH scores of patients who received one of three possible plating methods for arm wrestling fractures. These methods included single (posterior or lateral) and dual plating (Table 3).…”
Section: Treatment and Clinical Outcomesmentioning
confidence: 99%
“…Although the union time was shorter in patients who were applied the double-plate method, our union times were shorter compared to the literature. osteoporotic bones was the method that used eight lateral screws and six anterior screws for fixation (31). Therefore, in our study, this plate configuration was applied in patients who underwent double-plate fixation and early postoperative mobilization was initiated.…”
Section: Discussionmentioning
confidence: 99%
“…Murray et al, who popularized the use of the double-plate method in nonunion treatment, indicated that the double-plate method provides a stable fixation and has positive effects on fracture union (29). Biomechanical studies have shown that double-plate fixation provides more stable fixation than single-plate fixation and intramedullary nailing (30,31). One biomechanical study, which evaluated plate placement and plate length, found that the most stable fixation method for difference between the groups in terms of union time (p>0.05).…”
Section: Demographic Data Of the Patients Are Presented In Tablementioning
confidence: 99%